RGO@Cu2O@Cu Ternary Nanocomposite for High-Performance Non-Enzymatic Glucose Detection. Issue 8 (4th August 2021) - Pu, Fangzhao; Yu, Zhipeng; Lu, Wenjing; Kong, Chuncai; Lin, Ruijun; Bai, Xingyu; Zhang, Xiaojing; Lv, Jian; Yang, Zhimao
Abstract : Fast, reliable, and low-cost glucose detection methods are of great importance for the control of diabetes. In this study, Cu2 O combined with Cu nanoparticles anchored on reduced graphene oxide (RGO), was synthesized to function as the electrode in a non-enzymatic glucose sensor. The synergistic effect between Cu nanoparticles and Cu2 O, together with the high conductivity of RGO enabled considerably lower resistivity with greater glucose oxidation activity than pure Cu2 O. The RGO@Cu2 O@Cu electrode exhibited a high sensitivity of 1.112 mA mM −1 cm −2 with a detection limit of 0.019 μ M, and the linear range is up to 4 mM. Additionally, the RGO@Cu2 O@Cu electrode displayed good anti-interference performance within human blood and high stability while operating for a long duration. Significantly, the glucose detection capability of the as-designed electrode was comparable to commercial sensors, representing a valuable design for future non-enzymatic glucose sensing.